Pengembangan Media Pembelajaran Berbasis Android Pada Mata Pelajaran Teknologi Layanan Jaringan Untuk Medukung PJJ di Masa Pandemi Covid19 - Sanita, Debi; Maksum, Hasan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study aims to develop learning media and produce valid, practical and effective media on the subject of Network Service Technology for class XI Computer and Network Engineering students at SMK Negeri 8 Padang. This study uses an R&D design, with a four-D development model. The four-D development procedure is Define, Design, Development and Disseminate. The data analysis technique used is to describe the validity, practicality and effectiveness of the developed learning media. The results obtained from this development research are learning media based on Android. Based on the results of this research, it can be concluded that the developed media is declared valid on the media aspect of 0.86, the material aspect with a result of 0.95. The media that was developed was practical with the practical value of the teacher's response with results of 97.92% and student responses of 87.70%, and the Android-based learning media that was produced was effectively used with posttest results seen from students' classical completeness of 89% and gain score of 89% 0.44 with medium category. The conclusion is that the developed Android-based learning media can be used and feasible in the learning process to improve student learning outcomes.